Barriers and facilitators to the recruitment of disabled people to clinical trials: a scoping review - Sameed Shariq; Alexandra M Cardoso Pinto; Shyam Sundar Budhathoki; Marie Miller; Suzie Cro (Trials, 2023)
Abstract Introduction Underrepresentation of disabled groups in clinical trials results in an inadequate evidence base for their clinical care, which drives health inequalities. This study aims to review and map the potential barriers and facilitators to the recruitment of disabled people in clinical trials to identify knowledge gaps and areas for further extensive research. The review addresses the question: ‘What are the barriers and facilitators to recruitment of disabled people to clinical trials?’. Methods The Joanna Briggs Institute (JBI) Scoping review guidelines were followed to complete the current scoping review. MEDLINE and EMBASE databases were searched via Ovid. The literature search was guided by a combination of four key concepts from the research question: (1) disabled populations, (2) patient recruitment, (3) barriers and facilitators, and (4) clinical trials. Papers discussing barriers and facilitators of all types were included. Papers that did not have at least one disabled group as their population were excluded. Data on study characteristics and identified barriers and facilitators were extracted. Identified barriers and facilitators were then synthesised according to common themes. Results The review included 56 eligible papers. The evidence on barriers and facilitators was largely sourced from Short Communications from Researcher Perspectives (N = 22) and Primary Quantitative Research (N = 17). Carer perspectives were rarely represented in articles. The most common disability types for the population of interest in the literature were neurological and psychiatric disabilities. A total of five emergent themes were determined across the barriers and facilitators. These were as follows: risk vs benefit assessment, design and management of recruitment protocol, balancing internal and external validity considerations, consent and ethics, and systemic factors. Conclusions Both barriers and facilitators were often highly specific to disability type and context. Assumptions should be minimised, and study design should prioritise principles of co-design and be informed by a data-driven assessment of needs for the study population. Person-centred approaches to consent that empower disabled people to exercise their right to choose should be adopted in inclusive practice. Implementing these recommendations stands to improve inclusive practices in clinical trial research, serving to produce a well-rounded and comprehensive evidence base.